1999
DOI: 10.1007/s002469900478
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological Follow-Up of Tetralogy of Fallot

Abstract: Arrhythmias and sudden death are well-recognized complications that occur late after correction of tetralogy of Fallot. This study, based on the literature and personal work, reviews the numerous investigations prompted by these complications and provides recommendations regarding follow-up. Conduction disturbances and ventricular arrhythmias are both common; although mostly asymptomatic, they are the likely cause of syncopy and sudden death. Supraventricular arrhythmias are less common but cause symptoms more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 45 publications
0
21
1
Order By: Relevance
“…Data from TOF after repair suggest that asymptomatic Holter arrhythmia is not predictive of sudden cardiac death and we submit that most significant arrhythmias could be detected and reported here by 12 lead electrocardiograms and/or exercise testing and/or 24 h Holter monitoring [27,28]. Lack of right ventricular volumetric data and precise quantification of pulmonary regurgitation limits the ability of this study to conclude on the role of the latter.…”
Section: Study Limitationcontrasting
confidence: 56%
“…Data from TOF after repair suggest that asymptomatic Holter arrhythmia is not predictive of sudden cardiac death and we submit that most significant arrhythmias could be detected and reported here by 12 lead electrocardiograms and/or exercise testing and/or 24 h Holter monitoring [27,28]. Lack of right ventricular volumetric data and precise quantification of pulmonary regurgitation limits the ability of this study to conclude on the role of the latter.…”
Section: Study Limitationcontrasting
confidence: 56%
“…After TOF repair, induced VT correlates well with clinical sustained VT; programmed ventricular stimulation also guides drug therapy for clinical VT. EPS does not identify patients who are at risk of sudden death, however [110,111]. This probably is true in other congenital heart diseases postrepair [112].…”
Section: Congenital Heart Defectsmentioning
confidence: 97%
“…Murphy et al [2] and Silka et al [1] reported a 6% prevalence of late sudden cardiac death among patients with up to 30 years of follow-up. Important ventricular and atrial arrhythmias are also prevalent, occurring in up to 35% of patients [3][4][5]; Harrison et al [4] and Gatzoulis et al [6] reported risk factors for ventricular arrhythmia and sudden death, including repair at an older age, previous transannular patch repair, severe pulmonary regurgitation, right ventricular (RV) dilatation and dysfunction, RV outflow tract aneurysm, left ventricular (LV) systolic dysfunction, QRS duration !180 ms and increased QRS duration rate of change during follow-up [3]. A recent study showed that pulmonary regurgitation was the predominant lesion associated with ventricular tachycardia and sudden death [6].…”
Section: Introductionmentioning
confidence: 99%